Interfaith Jurisprudence and Ethics in the Modern Humanitarian Crisis: An Inclusive Legal-Theological Perspective - Abid Nurhuda; Ali Anhar Syi'bul Huda; Inamul Hasan Ansori (International Journal of Law and Political Authority, 2026)
This article examines the position and role of Islamic jurisprudence (fiqh) in responding to modern humanitarian crises through an interfaith ethical approach and inclusive theology. Contemporary humanitarian crises, including armed conflict, refugee crises, structural inequality, and global social vulnerability, require religions to transcend exclusive, internally oriented normative approaches. In this context, fiqh cannot be understood solely as a system of ritual and social law for Muslims, but needs to be reconstructed as a framework for dialogical and globally responsible humanitarian ethics. This research uses a qualitative approach based on a literature review, using Jasser Auda's systematic, normative-critical analysis of the maqasid of sharia and an inclusive theological perspective. The results of the study indicate that the internal plurality within the interfaith fiqh tradition holds significant ethical potential for building interfaith cooperation without sacrificing Islamic theological identity. Through the integration of the principles of maqasid al-sharīʿah, the value of human dignity, and universal humanitarian ethics, fiqh can function as a relevant moral medium in addressing global humanitarian challenges. This article asserts that the reconstruction of Islamic jurisprudence based on interfaith ethics is not a theological compromise, but rather an ethical ijtihad rooted in the Islamic scholarly tradition itself. Thus, Islamic jurisprudence has the potential to emerge as a normative tradition that is not only textually valid but also ethically meaningful and transformative in the contemporary plural world.